flrA, flrB and flrC regulate adhesion by controlling the expression of critical virulence genes in Vibrio alginolyticus - Gang Luo; Lixing Huang; Yongquan Su; Yingxue Qin; Xiaojin Xu; Lingmin Zhao; Qingpi Yan (Emerging Microbes and Infections, 2016)
Adhesion is an important virulence trait of Vibrio alginolyticus. Bacterial adhesion is influenced by environmental conditions; however, the molecular mechanism underlying this effect remains unknown. The expression levels of flrA, flrB and flrC were significantly downregulated in adhesion-deficient V. alginolyticus strains cultured under Cu2+, Pb2+, Hg2+ and low-pH stresses. Silencing these genes led to deficiencies in adhesion, motility, flagellar assembly, biofilm formation and exopolysaccharide (EPS) production. The expression levels of fliA, flgH, fliS, fliD, cheR, cheV and V12G01_22158 (Gene ID) were significantly downregulated in all of the RNAi groups, whereas the expression levels of toxT, ctxB, acfA, hlyA and tlh were upregulated in flrA- and flrC-silenced groups. These genes play a key role in the virulence mechanisms of most pathogenic Vibrio species. Furthermore, the expression of flrA, flrB and flrC was significantly influenced by temperature, salinity, starvation and pH. These results indicate that (1) flrA, flrB and flrC are important for V. alginolyticus adhesion; (2) flrA, flrB and flrC significantly influence bacterial adhesion, motility, biofilm formation and EPS production by controlling expression of key genes involved in those phenotypes; and (3) flrA, flrB and flrC regulate adhesion in the natural environment with different temperatures, pH levels, salinities and starvation time.Emerging Microbes & Infections (2016) 5, e85; doi:10.1038/emi.2016.82; published online 3 August 2016